Deep Learning in Defect Detection of Wind Turbine Blades: A Review - Masita, Katleho; Hasan, Ali N.; Shongwe, Thokozani; Abu Hilal, Hasan (IEEE-Inst Electrical Electronics Engineers Inc, 2025)
The increasing adoption of wind turbines as a key component of renewable energy generation necessitates the development of efficient and reliable maintenance strategies to ensure their optimal performance and safety. Among the most critical aspects of turbine maintenance is detecting and classifying defects in wind turbine blades, which are constantly exposed to extreme environmental conditions. Defects such as cracks, delamination, erosion, and icing not only compromise the structural integrity of blades but also significantly reduce their aerodynamic efficiency and energy production capabilities. While effective, traditional inspection methods are labor-intensive and time-consuming, prompting the exploration of automated solutions. This review paper examines the state-of-the-art deep learning methodologies applied to defect detection in wind turbine blades. Key advancements are highlighted, including the integration of Convolutional Neural Networks (CNNs), Variational Autoencoders (VAEs), and Generative Adversarial Networks (GANs) for image-based detection and anomaly identification. Additionally, transfer learning and attention mechanisms have been instrumental in enhancing the precision and speed of defect detection, enabling real-time applications. Notable approaches like YOLO (You Only Look Once) and its variants have shown exceptional performance in detecting defects with varying scales and complexities, leveraging innovations such as feature pyramid networks and efficient loss functions. Furthermore, this review discusses the role of advanced data acquisition techniques, such as drone-based imaging, thermographic analysis, and LiDAR (Light Detection and Ranging), in generating high-resolution and multi-spectral data for improved detection accuracy. Insights are provided into challenges such as class imbalance, limited labeled datasets, and environmental noise, alongside emerging solutions like semi-supervised learning and data augmentation. The paper concludes by emphasizing the transformative potential of deep learning in achieving automated, accurate, and efficient defect detection in wind turbine blades. Addressing current limitations through interdisciplinary research and innovative algorithms will pave the way for sustainable and cost-effective wind energy systems, ultimately contributing to the global transition toward renewable energy.
Keywords: Deep learning; Deep learning; defects; defects; wind turbine blades; wind turbine blades; wind farm; wind farm; drone; drone